Pengaruh Green Forest Campaign Message Dan Packaging Terhadap Brand Image Produk Innisfree Di Mall Central Park Jakarta Barat - Arin Valia; Rudy P.Tobing (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This Study ains to determine the effect of Green Forest Campaign Message and Packaging on Innisfree’s Brand Image. The sampel in this study were 89 respondents. The method of determining the sample in this study uses a simpler random sampling method. The data analysis method used is the Multiple Linear Regression method using the SPSS 26 program. The result of this study indicate that Green Forest Campaign Message has a positive and significant on Innisfree Brand Image, and Packaging has a positive and significant on Innisfree Brans Image and Green Forest Campaign Message and Packaging have a simultaneous effect on the Innisfree Brand Image.